Stratigraphy Analysis of the Nahr Umr Formation in Zubair oil field, Southern Iraq - Mohammed, Israa Imad; Alsultan, Hamid A. A. (Iraqi Journal of Science, 2023)
The Nahr Umr Formation is considered one of the main reservoirs produced in southern Iraq. It is one of the important siliciclastic deposits of the Cretaceous sequence of Iraq oilfields. Zubair oil fields ZB-190 and ZB-047 were chosen to study areas. This study depends on the available core and cutting samples to determine the facies analysis, depositional environments, petrographic characteristics and diagenesis processes. Based on the description of the core and the borehole, six types of facies were distinguished in the Nahr Umr Formation, resulting in an intercalated sandstone and shale with a thin layer of siltstone. The petrographic study of the clastic part of the Nahr Umr Formation showed that the sandstone is composed mainly of quartz arenite. Diagenesis processes affecting the Nahr Umr Formation are two types compaction and cementation processes. The sedimentary environment of the Nahr Umr Formation was represented by the deltaic fluvial environments. These environments appear in the central and southwestern parts of the study area. Sequence stratigraphy in the Nahr Umr Formation is beginning by sequence boundary type one (SB1) and sequence boundary type two (SB2) that appeared in the upper part of the formation. The other surfaces were represented by the end of the deposition of the Nahr Umr Formation and the emergence of the transgressive ravinement surface (TRS) within the transgressive system tract (TST)and The maximum flooding surface (MFS) was distinguished in the middle of the formation and each of these surfaces has a lateral extension along the study section.